072 Undergraduate nursing team; enhancing the learning environment for students. (December 2018) - Low, B; Byrne, J; Gowers, N; Howells, T; Porter, L; Robertson, S; Simpson, G
Abstract : Context: Student Nurses spend 2, 300 hours in practice placements gaining invaluable exposure to the intricate roles and responsibilities of a registered nurse. The need for all elements of practice to be conducive to learning is paramount. Assessment and guidance of students in practice is based on the availability of qualified staff but with ever increasing demands on nursing time often means less time dedicated to student learning. Description: The undergraduate nursing team consists of five band 6 nurses who cover the Trust. They are impartial from the students' assessment and are therefore excellently skilled resources to work with students who may be struggling or those students who may benefit from time dedicated to that next step. They support both students and assessors in practice and also act as a link to the students' higher education institute ensuing all support, information, and progress is transparent. The team is able to provide protected time for mentors to help create positive learning environments where critical analysis of clinical practice between student and assessor can take place. Observation: The team is a consistent source of support for the students and staff enabling the development of mutually professional relationships. Development of robust relationship between the undergraduate team and ward areas also provides a strong, positive network to improve student placement outcomes where necessary. Professional role modelling from the team helps to ensure students are exposed to safe practice, enhancing the care delivered to patients. Discussion: The presence of a dedicated education team for student nurses is greatly valued within the hospital and has a significant role in supporting both students and nurses to ensure the delivery of high-quality placement experiences. Literature indicates that positive placement experiences for all involved result in fair assessments of students.